Tracking multistability in the parameter space of a Chua’s circuit model - Nicolau N.S.* (2019)
© 2019, EDP Sciences / Società Italiana di Fisica / Springer-Verlag GmbH Germany, part of Springer Nature.Abstract: The effect of applying an asymmetric periodic continuous-feedback signal F(x), which is a function of voltage x, across one of the capacitors in the classical Chua’s circuit model is examined. We have performed a numerical investigation on the dynamics of the Chua’s circuit model to discuss a procedure of distorting, suppressing and moving attractors and stable periodic structures (SPSs) in phase and parameter spaces, respectively, by accordingly choosing the control parameters in the function F(x). Increasing the asymmetry strength in F(x), we are able to track and to move overlapped SPSs related to multistability phenomenon in phase space, and to suppress SPSs related to one single attractor. Our results indicate that the methodology used here will have a wide spectrum of applications in generic nonlinear complex dynamical systems presenting multistability, related to both theoretical and experimental issues.